Detecting orientational order in model systems by X‐ray cross‐correlation methods. (1st August 2014) - Lehmkühler, Felix; Grübel, Gerhard; Gutt, Christian
<x xml:space="preserve">Abstract</x> The results of a computational X‐ray cross‐correlation analysis (XCCA) study on two‐dimensional polygonal model structures are presented. This article shows how to detect and identify the orientational order of such systems, demonstrates how to eliminate the influence of the `computational box' on the XCCA results and develops new correlation functions that reflect the sample's orientational order only. For this purpose, the dependence of the correlation functions on the number of polygonal clusters and scattering vector magnitude q is studied for various types of polygons, including mixtures of polygons and randomly placed particles. An order parameter that describes the orientational order within the sample is defined. Finally, the influence of detector noise and nonplanar wavefronts on the XCCA data is determined, both of which appear to affect the results significantly and have thus to be considered in real experiments.